Imaging Low-Energy Ion Outflow in the Auroral Zone - Rowland, Douglas; Collier, Michael; Keller, John; Pfaff, Robert; Klenzing, Jeffrey; McLain, Jason; Clemmons, James; Hecht, James (Frontiers in Astronomy and Space Sciences, 2022)
The VISualizing Ion Outflow via Neutral atom imaging during a Substorm (VISIONS) sounding rocket mission investigated the factors leading to ion outflow following a geomagnetic substorm. In situ and remote sensing instrumentation provided complementary measurements that have been combined to yield an in-depth look at the phenomena associated with ion outflow. In particular, the inclusion of instrumentation that provided high spatial and temporal resolution “images” of low-energy neutral atom (ENA) emissions from the nightside auroral zone following a substorm has led to new insights. The observed ENAs were spatially structured, and strongly associated with regions of intense 630.0 nm auroral emissions. The ENAs in the auroral zone were predominantly up-going, consistent with thick-target scattering in the region where the ENA mean free path is close to or less than the atmospheric scale height.